Public Opinion Before the Event of the 2024 General Election - Wulandari, Margareta; Fariha, Naela Faza; Bintara, Chandra Satya; ., Mutiara (Universitas Telkom, 2024)
In Indonesia, which adheres to a democratic political system , public opinion becomes an important study because the democratic political system focuses on collective beliefs about the desires and interests of its people which can be drawn, accepted or aggregated into an idea called public opinion. Ahead of the 2024 election, the dynamics of public opinion in Indonesia are interesting, given that public trust in the performance of the General Elections Commission (KPU) has fluctuated along with political and economic dynamics. Likewise with public credibility towards parties which is a complex issue in line with Indonesia's political conditions ahead of elections which are often filled with sensitive issues. This research aims to map public perceptions of the 2024 election. This research will use a quantitative approach by taking the population on the island of Java. The required sample is 180 respondents who are evenly divided in 6 provinces with the non-proportional random sampling method. The theoretical approach used to dissect public perception is the ABC Theory approach which focuses on assessment of Attention, Behavior and Cognition. The combination of the three will show the dynamics of public perception ahead of the 2024 elections. Keywords: Perception, Election, Politics, Public, Government